Is Obesity related to Depression? - Sumera Gul1, Darakhshan Jabeen Hale2 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2020)
Objective: It is a well-known fact thatobesity as well as depression are two disorders that can lead to a number ofcommon health complications.Theassociation of depression with Body Mass Index in the Pakistani population has not been reported previously. The following study henceaims to understand the relationship of depression with various Body Mass Indexl Design: It is a descriptive study. Duration Dec 2017 - Feb 2018 Methodology:Males and females in different Body Mass Index groups with and without depression were compared. Results: Results show that moderate depression is most common among the population of Pakistan. Most of the obese men as well as women are depressed. There is also higher percentage of depression in underweight men. This finding is not seen in underweight women. Conclusion: There is a strong association of extremes of Body Mass Index with depression in male population. However, women population is more prone to develop depression with higher Body Mass Index. Depression in males is largely associated with obesity and sometimes underweight Body Mass Index but in the females, depression is associated with overweight Body Mass Indexand obesity but not with extreme low Body Mass Index. More detailed studies are required to assess the comorbid related to these leading health issues.